Fe/W Co‐Doped BiVO4 Photoanodes with a Metal–Organic Framework Cocatalyst for Improved Photoelectrochemical Stability and Activity. Issue 19 (30th August 2016) - Jiao, Zhengbo; Zheng, Jingjing; Feng, Chenchen; Wang, Zeli; Wang, Xuesen; Lu, Gongxuan; Bi, Yingpu
Abstract: BiVO4 has been identified as one of the excellent visible light responsive photoanodes for use in photoelectrochemical (PEC) water splitting. However, pristine BiVO4 usually exhibits relative low photocatalytic properties owing to insufficient charge separation and transport characteristics. Although the marginal n‐type doping of higher valence ions can obviously raise the photocurrent value, it by no means improves the PEC stability. In this work, we successfully enhanced the PEC stability of BiVO4 by doping Fe ions in substitution of Bi. Density functional theory calculations have illustrated that Fe‐doping would result in an impurity band in the forbidden gap, and thus narrow its energy gap. More importantly, Fe‐doping can synergize with other means to further improve the PEC activities of BiVO4 . Therefore, we fabricated a nanoporous Fe/W co‐doped BiVO4 photoelectrode, and then loaded the metal–organic framework (MOF) MIL‐100(Fe) as cocatalyst to further promote the separation of charge carriers. To the best of our knowledge, MOFs have not yet been utilized as a cocatalyst to facilitate the charge separation, which could increase the photocurrent density of Fe/W co‐doped BiVO4 . Abstract : It does it all : The photoelectrochemical stability issue of BiVO4 was successfully resolved by Fe‐doping, which can synergize with other means to further improve the PEC activity of BiVO4 . Here, a nanoporous Fe/W co‐doped BiVO4 photoelectrode modified with a metal–organic framework (MOF) cocatalyst is introduced to further promote the PEC stability and activity.